Bermisi Dalam Basis Digital Sebagai Transformasi Misi Kristen Di Era Revolusi Industri 4.0 - Delpi Novianti; Alon Mandimpu Nainggolan (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2022)
The writing of this scientific paper is motivated by the progress and development of technology in the era of the industrial revolution 4.0 which has converted various forms of human activity into a digital and machine basis. This paper aims to produce a mission on a digital basis as a reflection of a transformative mission to proclaim the gift of salvation from God in the midst of human life in the era of the industrial revolution 4.0 in order to expand the kingdom of God. To realize the research objectives, the author uses a descriptive qualitative research method. Through this research, it was found that the strategy, method, or mission approach can be transformed according to the changing times, especially in the era of the industrial revolution 4.0 to present a mission that is relevant without reducing the value of the truth of the gospel. Carrying out a mission in a broad sense means that we are giving ourselves to respond to God's grace to be witnesses, salt, and light in this world. This mission in the era of the industrial revolution 4.0 is carried out to reach souls by taking advantage of the advantages of digital that are not limited by space and time so that news about the kingdom of God is increasingly expanded, this news will reach anyone anywhere. In addition, missions on a digital basis can be applied as a form of service to the congregation to maintain and maintain the faith of believers. So the various digital devices that exist today do not become idols for human life which only have a negative impact. However, various digital devices it is used to bring the glory of God into the midst of the world.